Review on high-performance air cathode microbial fuel cell for power generation and COD reduction - Samuel Reinhard Ignatius Sitorus,; Mimi Hani Abu Bakar,; Edy Herianto Majlan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The world population is projected to increase by one billion for the next ten years from the year 2016. Unfortunately, global power plants still using non-renewable energy sources. Consumption of fossil fuels harms the environment, while nuclear energy could release a significant amount of radioactive material. Besides the energy issues, the growth in population contributes to the high production of wastewater. Every year, the wastewater treatment industry consumes a high input of energy for treatment purposes. These issues invigorate research interest in microbial fuel cell (MFC) technology that can generate green power electricity while breaking down the organic matter in the wastewater. One of the research advancement in MFC is the air-cathode MFC that is scaled-up friendly due to its simple structure, and ability to utilize the abundance of oxygen in the air as the membrane and scaling up arrangements. Therefore, this review aims to discuss the main positive findings contributing to the recent improvement of air-cathode MFC and the obstacles faced for upscaling.